Deciphering insights into commercial Myrrh species authenticity from the psbA-trsnH genetic region - Changhong Cao; Wenting Zhong; Feng Gao; Ying Zhang; Zhiguo Ma; Hui Cao; Menghua Wu (PLoS ONE, 2025)
Objective The genetic analysis, particularly focusing on the psbA-trnH region, aims to tackle the challenges linked to myrrh identification and improve quality control in medicinal and aromatic plant sectors. This process reveals the genetic diversity inherent in myrrh species, identifies adulterants, and assesses consistency with pharmacopoeia-designated species. Methods A meticulous investigation was conducted, involving twenty-five myrrh samples sourced from diverse origins and one adulterant sample. The methodology encompassed precise execution of DNA extraction, PCR amplification targeting the psbA-trnH region, sequencing, and subsequent data analysis. Additionally, the integration of GenBank data was employed to enrich the genetic analysis. Results The psbA-trnH region demonstrated 100% amplification efficiency across all myrrh samples, accurately identifying three distinct species—Commiphora gileadensis, Commiphora myrrha, and Commiphora edulis. Only 8% of samples aligned with pharmacopoeia-specified species, revealing a significant misalignment. The identified adulterant, Liquidambar formosana, underscored the efficacy of the genetic approach. Genetic distances and haplotype analysis offered insights into myrrh species diversity. Intraspecific and interspecific distances highlighted the discriminatory potential of the psbA-trnH region. A phylogenetic tree illustrated distinct genetic clusters among Commiphora species and Liquidambar formosana. Conclusions It affirms the robustness of the psbA-trnH region for authenticating myrrh and emphasizes the necessity of adapting pharmacopoeial standards to accurately mirror genetic diversity. An avenue for exploring therapeutic variations within myrrh species and advocates collaboration among researchers, regulatory agencies, and industry stakeholders to fortify comprehensive quality management measures within the context of agronomy-focused herbal products.